Impact of supply strategies of ACI Animal Health: evaluation of supply chain performance of ACI animal health business - Silvi, Asfika Nusrat (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.